RESET Initiative®: Practical strategies for supporting educators and students - Pabers, Christina; Walsh, Thérèse (Allies for Education, 2020)
The RESET Initiative® is an online or live, 7-minute per day, Social and Emotional Learning program designed to support educators, students, and families. RESET, which stands for Respiratory Exercises for Social and Emotional Teaching, originated in Mexico City under the name of Más Respiración Consciente and continues to be implemented there in Kindergarten through 12th grade. The techniques that make up RESET are aligned with the five social and emotional competencies identified by Collaborative for Academic, Social, and Emotional Learning (CASEL). This article highlights some of the key features of RESET and the experiences of educators and students in schools in the US.